2010
DOI: 10.1370/afm.1188
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Primary Care Visit Patterns

Abstract: PURPOSE Many clinical preventive care services are recommended for adolescents. Little is known about whether most adolescents have a suffi cient number of preventive care services visits over time to receive those services. We wanted to measure how frequently adolescents who are insured either through private insurance or government programs have preventive vs nonpreventive care visits. METHODSWe conducted a retrospective descriptive analysis based on claims data from a large health plan in Minnesota with abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 8 publications
1
118
2
Order By: Relevance
“…The study by Nordin et al reinforces the observation that access and care continuity can be illusive, particularly for certain types of patients. 6 They use data from a large regional health system to describe the use of preventive services by adolescents and reinforce our perception that adolescents rarely use physician offi ces for preventive care during their teenage years. Our door may be open, but adolescents don't enter for a variety of reasons.…”
Section: Getting To the Doctor-or Notmentioning
confidence: 79%
“…The study by Nordin et al reinforces the observation that access and care continuity can be illusive, particularly for certain types of patients. 6 They use data from a large regional health system to describe the use of preventive services by adolescents and reinforce our perception that adolescents rarely use physician offi ces for preventive care during their teenage years. Our door may be open, but adolescents don't enter for a variety of reasons.…”
Section: Getting To the Doctor-or Notmentioning
confidence: 79%
“…48,51 One analysis based on claims data from a 700 000-member health plan in Minnesota revealed that one-third of adolescents with 4 or more years of continuous enrollment had no preventive care visits from age 13 through 17 years, and another 40% had only a single preventive care visit. 52 National surveys with past-year preventive visit measures show significant variation across adolescents (43% to 81%) and young adults (26% to 58%). 53 Those with behavioral health diagnoses are especially lacking in access to care, as fewer than half of all adolescents with psychiatric disorders received care within the past year.…”
Section: Primary Care Access and Utilizationmentioning
confidence: 99%
“…[27][28][29] Furthermore, those from disadvantaged backgrounds are at the highest risk of not having regular health maintenance visits or receiving needed mental health care. 27,[29][30][31] Many adolescents also tend to engage in health behaviors that place them at risk for the leading causes of morbidity and mortality. 32 As adolescents begin to gain greater independence and assume individual responsibility for daily health habits, develop new social relationships, and individuate from their parents, these changes bring new opportunities and challenges for improving health and preventing disease.…”
Section: Responding To the Unique Needs Of Adolescentsmentioning
confidence: 99%